GREEN ECONOMY AND ISLAMIC FINANCE: CROSSING A SUSTAINABLE PATH IN ECONOMIC DEVELOPMENT - Siregar, Muhammad Rafi; Martian, Indra; Rijadi, Puti Khairani (Al-Infaq: Jurnal Ekonomi Islam, 2023)
This article presents a holistic view of the concept and integration between Green Economy and Islamic Finance in an effort to cross sustainable paths in economic development. The Green Economy, which focuses on sustainable and environmentally sound growth, meets with Islamic Finance principles that prohibit usury and promote social justice. The article also discusses how this integration can support the financing of sustainable projects, especially in the development of green infrastructure and the empowerment of local communities. The method used in this study is qualitative research. The descriptive qualitative research in this study has clarity in its specific purpose, which is to investigate and describe how the integration of Green Economy and Islamic Finance can contribute to sustainable economic development. By discussing the alignment of green economy principles and Islamic finance, this article provides a deep understanding of how this integration can form a sustainable path that not only benefits the economy, but also respects Islamic moral and ethical values.Findings reveal a significant positive impact on economic development, emphasizing environmental stewardship, long-term sustainability, community empowerment, and economic justice, all while respecting Islamic moral and ethical values. This integration not only benefits the economy but also enhances the overall stability and resilience of the financial system.